Values of abdominal perimeter and waist-hip ratio in patients with hypertension - Ángel Alfonso Ximelis Morales; Vivian Queralta Mazar; Marilú Ferrer Ramírez; Aileen Vega Riveri; Carlos Ernesto Quintana Batista (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Hypertension constitutes a problem of public health in almost all over the world. Among the risk factors associated with it, the accumulation of fat is notable, which can, in turn, establish risks and determine comorbidities and mortality associated with this nosological entity. Objective: To determine the variations in the values of the abdominal perimeter and waist-hip ratio in patients with hypertension, according to selected epidemiological and clinical variables. Methods: A descriptive, prospective and cross-sectional study was carried out on 221 patients with hypertension, belonging to doctor's office 19 of Josué País García Teaching Polyclinic in Santiago de Cuba municipality, from June, 2019 to December, 2020. Results: There was a prevalence of the female sex and the 65-74 age group (28.5%). The anthropometric indicators, abdominal perimeter and waist-hip ratio, had values that exceeded the established normal parameters for both sexes. The calculation of the abdominal perimeter revealed a predominance of obesity in the female sex, while it was classified as increased in the male sex. Conclusions: The values of the waist-hip ratio and abdominal perimeter exceeded those classified by the World Health Organization as high risk of presenting the disease in both sexes.